Pengaruh Perbandingan Tepung Terigu dan Daging Ikan Betok (Anabas testudineus) terhadap Sifat Kimia dan Sensori Mi Basah - Sussi Astuti; Siti Inayah; Dewi Sartika; Esa Ghanim Fadhallah (Universitas Djuanda, 2026)
Substitution of wheat flour with climbing perch (Anabas testudineus) meat is one of the food diversification efforts to increase the nutritional value of wet noodles, especially protein content. This study aims to determine the best ratio between wheat flour and climbing perch meat in making wet noodles based on chemical and organoleptic characteristics. The study was arranged using a single factor in a Completely Randomized Block Design (RAKL) with four replications. The treatments tested consisted of six ratios of wheat flour (TT) and climbing perch meat (DIB), namely A0 or control (100%:0%), A1 (95%:5%), A2 (90%:10%), A3 (85%:15%), A4 (80%:20%), and A5 (75%:25%). Data were analyzed using analysis of variance, followed by an Honestly Significant Difference (HSD) test at the 5% level. The results showed that treatment A2 with a TT:DIB ratio of 90%:10% was the best treatment. This treatment produced wet noodles with a water content of 50.40%, a protein content of 6.27%, a savory taste score of 3.17, a white color score of 3.10, a non-sticky and chewy texture score of 3.17, and an overall acceptability score of 3.48. Based on these results, climbing perch meat can be used as a substitute for wheat flour at a 10% level to produce wet noodles with better protein content and sensory characteristics that are still acceptable to panelists.